Dietary Intake Patterns of Alcoholics; A Case Study of Selected Rehabilitation Centers in Kenya - Amanya Mutuli, Lucy; Bukhala, Peter; Nguka, Gordon (International Journal of Nutrition, 2020)
Introduction Sub-optimal dietary intake patterns have a major detrimental impact on the nutritional status of an alcoholic. These patterns exacerbate the status of alcoholism and the functioning of the alcoholic’s body. Objective This study aimed to examine alcoholic’s dietary intake patterns. Methods A cross-sectional study was conducted on 204 alcoholics undergoing alcohol rehabilitation in selected rehabilitation centers. A 24 hour food recall and food frequency questionnaire was used to assess dietary intake of the respondents. Factor analysis of food items and groups, cluster analysis of dietary intake patterns, and multivariate regressions were carried out. Results Three dietary intake patterns were identified among alcoholics namely a low calorie intake (described mainly by consumption of plant-based foods); a composite intake (distinguished by adequate consumption of both plant-based and animal-based foods) and a high calorie intake (characterized by high consumption of animal-based foods). Conclusion Optimal dietary intake promotion programs are needed to address the dietary intakes of recuperating alcoholics under rehabilitation to help prevent malnutrition and other associated comorbidities.
Keywords: Dietary Intake Patterns; Alcoholics; Rehabilitation Centers; Nutritional Status; Food Frequency Questionnaire